Recognition of Apoptotic Cells by Epithelial Cells: CONSERVED VERSUS TISSUE-SPECIFIC SIGNALING RESPONSES - Patel, Vimal A. (American Society for Biochemistry and Molecular Biology, 2010)
During apoptosis, cells acquire new activities that enable them to modulate the fate and function of interacting phagocytes, particularly macrophages (mϕ). Although the best known of these activities is anti-inflammatory, apoptotic targets also influence mϕ survival and proliferation by modulating proximal signaling events, such as MAPK modules and Akt. We asked whether modulation of these same signaling events extends to epithelial cells, a minimally phagocytic cell type. We used BU.MPT cells, a mouse kidney epithelial cell line, as our primary model, but we also evaluated several epithelial cell lines of distinct tissue origins. Like mϕ, mouse kidney epithelial cells recognized apoptotic and necrotic targets through distinct non-competing receptors, albeit with lower binding capacity and markedly reduced phagocytosis. Also, modulation of inflammatory activity and MAPK-dependent signaling by apoptotic and necrotic targets was indistinguishable in kidney epithelial cells and mϕ. In contrast, modulation of Akt-dependent signaling differed dramatically between kidney epithelial cells and mϕ. In kidney epithelial cells, modulation of Akt was linked to target cell recognition, independently of phagocytosis, whereas in mϕ, modulation was linked to phagocytosis. Moreover, recognition of apoptotic and necrotic targets by kidney epithelial cells elicited opposite responses; apoptotic targets inhibited whereas necrotic targets stimulated Akt activity. These data confirm that nonprofessional phagocytes recognize and respond to dying cells, albeit in a manner partially distinct from mϕ. By acting as sentinels of environmental change, apoptotic and necrotic targets may permit neighboring viable cells, especially non-migratory epithelial cells, to monitor and adapt to local stresses.